Oxidant/anti-oxidant status, lipid peroxidation and nitric oxide in primary fibromyalgia syndrome and the effect of anti-depressant treatment - Ozgocmen, S; Ardicoglu, O; Yildizhan-Bulut, H; Ozyurt, H; Sogut, S (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL